WASATHIYAH IQTISHADIYAH SEBAGAI PARADIGMA PEMBANGUNAN EKONOMI ISLAM - Makhsusi Zakiyah; Sukandi Sukandi (Iltizam : Jurnal Ekonomi dan Keuangan Islam, 2026)
Islamic economic development requires a paradigm that not only emphasizes economic growth but also integrates the values of justice, balance, public welfare, and sustainability. To date, Wasathiyah Iqtishadiyah has predominantly been understood as a principle of moderation in economic activities, while its position as a paradigm of Islamic economic development has not been comprehensively conceptualized. This article aims to analyze and reconstruct Wasathiyah Iqtishadiyah as a paradigm of Islamic economic development through a systematic conceptual approach. The study employed a qualitative approach using a library research method. Data were collected from secondary sources, including books, scientific journal articles, conference proceedings, dissertations, and academic documents related to Wasathiyah Iqtishadiyah, Islamic economic development, and maqashid al-shari'ah. The data were analyzed using content analysis and conceptual analysis through data reduction, thematic classification, interpretation, and conceptual synthesis. The findings reveal that Wasathiyah Iqtishadiyah possesses the characteristics of an Islamic economic development paradigm by integrating the principles of balance (tawazun), justice ('adl), moderation (wasathiyah), public welfare (maslahah), sustainability, and the objectives of Islamic law (maqashid al-shari'ah). This paradigm offers a holistic development approach that combines economic, social, moral, spiritual, and ecological dimensions, thereby emphasizing not only economic growth but also equitable welfare distribution and the improvement of human well-being. This study contributes conceptually by reconstructing Wasathiyah Iqtishadiyah as a paradigm of Islamic economic development, enriching the theoretical foundation of Islamic economics while providing a conceptual basis for formulating inclusive, equitable, and sustainable development policies.